Pemberdayaan Masyarakat Melalui Program Pengabdian Dalam Peningkatan Literasi Siswa Di SDN 2 Korleko Selatan: English - Imam Hidayatullah; Firman Zandra Gholib; Sania Salsabila Mardita; Lokia Lusiana; Fina Meliana; M. Samdya Aripansy; Neli Apriani; Nurul Ainun; Yudiva Damar Basmalla; Made Sutha Yadnya; Sania Salsabila Mardita (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Basic education in Korleko Selatan Village still faces challenges, particularly related to low student literacy skills, which are influenced by the socio-economic conditions of their families and limited learning support at home. This situation makes the children's learning process highly dependent on school and not yet fully optimal. To overcome this, PMD KKN students from Mataram University carried out intensive learning assistance activities while also providing informal literacy assistance facilities at the KKN post, in an effort to strengthen student literacy. This activity aimed to improve children's reading skills while also building interactive literacy habits, both in the school environment and in the village. The activity was carried out through reading guidance, interactive educational games, and a reading corner at the KKN post. The results obtained show an increase in reading fluency and student participation, thus supporting equitable basic education and fostering optimal learning motivation. Keywords: literacy, KKN PMD, SDN 2 Korleko Selatan, learning assistance